1937
DOI: 10.1113/jphysiol.1937.sp003455
|View full text |Cite
|
Sign up to set email alerts
|

The changes in viscosity of an unstriated muscle (Mytilus edulis) during and after stimulation with alternating, interrupted and uninterrupted direct currents

Abstract: MUSCLE viscosity influences the response to a stimulus in two ways, by opposing rapid shortening or development of tension, and by retarding relaxation. The importance of the former is illustrated by the large reduction in viscosity undergone by the retractor penis of the dog when stimulated with adrenaline [Winton, 1930]: the muscle is changed from a condition in which it is capable of resisting external forces passively and economically, to one in which it can pull relatively powerfully and quickly. The impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1941
1941
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…when the acetylcholine is removed) the tension-length relationship of the muscle changes from the form shown by curve C in Fig. 8 to that shown by curve B, and this seems to correspond with the variations in 'viscosity' and 'plasticity' described by Winton (1937) and Johnson (1954), respectively. In the present experiments, it was not possible to determine the time course with which this change takes place, because the muscle had to be washed thoroughly after the acetylcholine was removed; all one can say is that the change is complete within a few minutes.…”
Section: Tonic Responsementioning
confidence: 55%
“…when the acetylcholine is removed) the tension-length relationship of the muscle changes from the form shown by curve C in Fig. 8 to that shown by curve B, and this seems to correspond with the variations in 'viscosity' and 'plasticity' described by Winton (1937) and Johnson (1954), respectively. In the present experiments, it was not possible to determine the time course with which this change takes place, because the muscle had to be washed thoroughly after the acetylcholine was removed; all one can say is that the change is complete within a few minutes.…”
Section: Tonic Responsementioning
confidence: 55%
“…There is then a gap, presumably due to World War I, that extends until a second burst of work from 1928 to 1943 on a variety of catch-producing molluscan muscles (von Uexküll, 1926;Bozler, 1928Bozler, , 1930Bozler, , 1931aBozler, , 1936Bayliss et al, 1930;Jordan, 1931;van Overbeek, 1931;Herter, 1931a,b;Fletcher, 1937;Winton, 1937;van Dijk, 1937;Pumphrey, 1938;Singh, 1938aSingh, ,b, 1943. These papers showed that these muscles could produce both rapidly and slowly relaxing contractions, depending on the details (alternating or direct current, respectively) of the electrical stimulation used.…”
Section: Unique Properties Due To Acto-myosin Interaction 1: Catchmentioning
confidence: 99%
“…It is therefore interesting to recall that in certain types of smooth muscle stimulation may cause a relaxation of existing tension without, subsequently, producing a positive tension development. It has been known for many years (Winton, 1937) that the anterior byssus retractor muscle of Mytilus edulis, when it is in a state of tonic contraction, can be made to relax by the application of an alternating current stimulus. Also, in the resting Mytilus muscle it has been shown that the tension caused by stretching can be partially released by repetitive stimulation (Lowy & Millman, 1963).…”
Section: Discussionmentioning
confidence: 99%